THE EFFECT OF SHOPEEPAY-BASED MARKETING AND PAYMENT GATEWAY STRATEGIES ON FINANCIAL INCLUSION OF SHOPEE APPLICATION USERS IN DKI JAKARTA - Sofi Windiarti; Harya Kuncara Kuncara W; Aditya Pratama (Transpublika Publisher, 2022)
This study aims to determine the effect of marketing strategy (x1) and shopeepay-based payment gateway on financial inclusion (y1) of Shopee application users in DKI Jakarta. This study is associative research using primary data that is directly the result of a questionnaire or survey from respondents with an unknown population and the researchers took 260 samples, namely Shopee application users in DKI Jakarta who always or have used shopeepay as a payment method when shopping online. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that marketing strategy (x1) has a significant positive effect on financial inclusion (y) then the level of financial inclusion of Shopee application users in DKI Jakarta will increase and the shopeepay-based payment gateway variable (x2) also has a significant positive effect on financial inclusion (y). Based on the results of the analysis, with the existence of a good marketing strategy carried out by the Shopee application can increase financial inclusion. Students can apply the implications of marketing strategies carried out by the Shopee application when they want to do business or entrepreneurship. In the other side, the influence of this marketing strategy can make someone more impulse buying and consumptive.